Fengycins From Bacillus amyloliquefaciens MEP218 Exhibit Antibacterial Activity by Producing Alterations on the Cell Surface of the Pathogens Xanthomonas axonopodis pv. vesicatoria and Pseudomonas aeruginosa PA01 - Medeot, Daniela B.; Fernandez, Maricruz; Morales, Gustavo M.; Jofré, Edgardo (Frontiers in Microbiology, 2020)
Bacillus amyloliquefaciens MEP218 is an autochthonous bacterial isolate with antibacterial and antifungal activities against a wide range of phytopathogenic microorganisms. Cyclic lipopeptides (CLP), particularly fengycins, produced by this bacterium; are the main antimicrobial compounds responsible for the growth inhibition of phytopathogens. In this work, the CLP fraction containing fengycins with antibacterial activity was characterized by LC-ESI-MS/MS. In addition, the antibacterial activity of these fengycins was evaluated on the pathogens Xanthomonas axonopodis pv. vesicatoria (Xav), a plant pathogen causing the bacterial spot disease, and Pseudomonas aeruginosa PA01, an opportunistic human pathogen. In vitro inhibition assays showed bactericidal effects on Xav and PA01. Atomic force microscopy (AFM) images revealed dramatic alterations in the bacterial surface topography in response to fengycins exposure. Cell damage was evidenced by a decrease in bacterial cell heights and the loss of intracellular content measured by potassium efflux assays. Furthermore, the viability of MRC-5 human normal lung fibroblasts was not affected by the treatment with fengycins. This study shows in vivo evidence on the less-known properties of fengycins as antibacterial molecules and leaves open the possibility of using this cyclic lipopeptide as a novel antibiotic.